Guide to the production of High-Quality Cassava Peel® mash as a livestock feed in Nigeria - CGIAR Research Program on Livestock (2019)
Factories have been established in Nigeria, based on the guidelines. From data collected in 2019, 4,800 tonnes of HQCP mash was produced and distributed by feed manufacturers who received technical training from ILRI. UPDATE: By the end of the CRP in 2021, 22 new factories had been established. https://www.ilri.org/news/waste-wealth-innovation-turning-cassava-peels-growing-new-industry https://repo.mel.cgiar.org/handle/20.500.11766/13033